Inhibitory Effect of Aconitine on Colorectal Cancer Malignancy via Inducing Apoptosis and Suppression of Cell Motion - Li, Xuehui; Hu, Jianglin; Tong, Duan; Yang, Taotao; Deng, Ming (Turkish Journal of Gastroenterology, 2025)
Background/Aims: The incidence of colorectal cancer (CRC) has been increasing in recent years worldwide. Aconitine is a diester diterpenoid alkaloid that exhibits an antitumor role in several cancers. Nevertheless, it remains unclear whether aconitine also has antitumor activity in CRC. This study aims to investigate the effects of aconitine on the malignant behaviors of CRC cells. Materials and Methods: 3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide (MTT) assay was utilized for cell viability assessment. Flow cytometry, western blotting, wound healing, and Transwell assays were implemented for examining the aconitine effect on CRC cell apoptosis, migration, and invasiveness. Animal experiments were performed to further elucidate aconitine’s effect on CRC tumorigenesis. Results: Aconitine time- and dose-dependently restrained CRC cell viability but was not cytotoxic to normal colorectal mucosa cells. Aconitine facilitated CRC cell apoptosis and hindered cell migration and invasiveness. Aconitine blocked tumor growth in xenograft mouse models. Conclusion: Aconitine exerts an anti-CRC effect by promoting cell apoptosis and blocking cell migration and invasiveness. Cite this article as: Li X, Hu J, Tong D, Yang T, Deng M. Inhibitory effect of aconitine on colorectal cancer malignancy via inducing apoptosis and suppression of cell motion. Turk J Gastroenterol. 2025;36(1):53-60.